REBACIN® is an optional intervention for persistent high‐risk human papillomavirus infection: A retrospective analysis of 364 patients. Issue 1 (13th October 2020) - Yang, Ying; Hu, Tingwenyi; Ming, Xiu; Yang, E.; Min, Wenjiao; Li, Zhengyu
Abstract: Objective: To evaluate the therapeutic efficacy of REBACIN® in patients with persistent high‐risk HPV (hrHPV) infection. Persistent hrHPV infection is a crucial cause of cervical cancer, for which optimal pharmacological intervention remains unavailable. Methods: A retrospective analysis and a meta‐analysis were carried out. The retrospective analysis included 364 patients who were persistently infected with HPV for at least 12 months, between September 2015 and February 2019, and only received the REBACIN® intervention. HPV DNA typing, HC2 hrHPV DNA, and ThinPrep cytologic tests were performed before and after the REBACIN® intervention, to evaluate the therapeutic efficacy. The meta‐analysis included trials evaluating the therapeutic efficacy of interferons. Results: After a follow‐up period of 3–6 months, the overall rate of efficacy of REBACIN® was 74.73% (272/364), which was higher than that of interferon (61.50%). The efficacy of REBACIN® was correlated with HPV type (odds ratio [OR] 0.549, 95% confidence interval [CI] 0.367–0.822, P =0.004) and pretreatment cytology (OR 0.358, 95% CI 0.173–0.739, P =0.005). Conclusion: REBACIN® is potently efficacious at clearing persistent hrHPV infection; hence, it can serve as an optional intervention for persistent hrHPV infection. Abstract : REBACIN® is potently efficacious at clearing persistent high‐risk human papillomavirus infection and could serve as an optional intervention.